Dryland Sorghum Nitrogen Management: Implications for Utilization as Ethanol Feedstock - K. A. Gehl; L. Haag; J. Warren; S. Sharma; P. J. Tomlinson (Kansas Agricultural Experiment Station Research Reports, 2020)
A study was initiated in 2018 to collect preliminary data to quantify nitrous oxide (N2O) emissions from dryland grain sorghum in western Kansas. Results indicate that the greatest flux of N2O occurred within the first 14 days after fertilization when plant uptake was minimal and soil moisture was elevated. During this time period, the timing and amount of rainfall was critical with respect to N2O flux. Nitrous oxide flux during the fallow phase was negligible. The cumulative emissions factor for fertilizer-derived N2O estimated for Colby ( 0.3%) is well below the Intergovernmental Panel on Climate Change (IPCC) default estimate of 1.0%. These preliminary factors are very promising for documenting the sustainability of dryland grain sorghum as biofuel feedstock.
Keywords: grain sorghum; dryland; nitrogen management; nitrous oxide emissions